BUSANA FUTURISME UNTUK WANITA - Wong, Henny; Muladi, Edy (Anggada : Jurnal Desain dan Seni, 2021)
Clothing is one of the basic human needs, nowadays the need has developed into the need for LifeStyle, which was influenced by place, time and special occasion. In General, the participants of such event are influential people who use unusual Avant-Garde Fashion as self-identity. Because Avant-Garde itself is a term for “vanguard’ or “fore-guard”, or people that are on the front line. This principal has similarity with Futurism that adores ‘dynamism’. The Writer was inspired to ‘bridge’ the two understanding, explore and identify fashion visual using the Principle of Two-Dimensional Design and Gestalt Theory. Subsequently designing a fashion piece which’s visual concept are based on the Principle of Two-Dimensional Design and Gestalt Theory to produce a fashion piece that has the impression of the Futurism art movement.